2016
DOI: 10.1111/evo.12897
|View full text |Cite
|
Sign up to set email alerts
|

Partially repeatable genetic basis of benthic adaptation in threespine sticklebacks

Abstract: The extent to which convergent adaptation to similar ecological niches occurs by a predictable genetic basis remains a fundamental question in biology. Threespine stickleback fish have undergone an adaptive radiation in which ancestral oceanic populations repeatedly colonized and adapted to freshwater habitats. In multiple lakes in British Columbia, two different freshwater species have evolved: a deep-bodied benthic form adapted to forage near the lake substrate, and a narrow-bodied limnetic form adapted to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 88 publications
6
49
0
Order By: Relevance
“…In a model that somewhat reconciled the theoretical debate, Orr [56] predicted that a few mutations of large effect and many of smaller effect would contribute to the process of adaptation. Previous analyses of the distribution of effect sizes of QTL identified for body shape and skeletal traits in stickleback provide qualitative support for Orr's model [29,33,42,47]. With data on the per cent variance explained (PVE) for 1034 QTL from the 28 published QTL studies in threespine stickleback, we now have a larger sample size to examine this distribution (figure 2).…”
Section: Identification Of Quantitative Trait Loci Revealsmentioning
confidence: 74%
“…In a model that somewhat reconciled the theoretical debate, Orr [56] predicted that a few mutations of large effect and many of smaller effect would contribute to the process of adaptation. Previous analyses of the distribution of effect sizes of QTL identified for body shape and skeletal traits in stickleback provide qualitative support for Orr's model [29,33,42,47]. With data on the per cent variance explained (PVE) for 1034 QTL from the 28 published QTL studies in threespine stickleback, we now have a larger sample size to examine this distribution (figure 2).…”
Section: Identification Of Quantitative Trait Loci Revealsmentioning
confidence: 74%
“…Nevertheless, several studies indicate that adaptation to novel aquatic environments may also involve parts of the genome outside these large target regions (DeFaveri et al 2011; Leinonen et al 2012; Ellis et al 2015; Erickson et al 2016; Ferchaud and Hansen 2016). The QTL underlying physiological adaptations to different aquatic environments in sticklebacks have not been well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…We overlaid positional information for genomic islands with those of Ensembl predicted genes (Jones et al 2012b) and with previously identified quantitative trait loci (QTL), candidate genes, expression outliers and outlier regions (Peichel et al 2001;Colosimo et al 2004Colosimo et al , 2005Cresko et al 2004;Shapiro et al 2004;Kimmel et al 2005;Coyle et al 2007;Miller et al 2007Miller et al , 2014Albert et al 2008;Makinen et al 2008a,b;Chan et al 2009Chan et al , 2010Kitano et al 2009Kitano et al , 2010Kitano et al , 2013Hohenlohe et al 2010;DeFaveri et al 2011;Greenwood et al 2011Greenwood et al , 2012Greenwood et al , 2013Greenwood et al , 2015Shimada et al 2011;Deagle et al 2012;Jones et al 2012a,b;Kaeuffer et al 2012;Malek et al 2012;Rogers et al 2012;Wark et al 2012;Arnegard et al 2014;Berner et al 2014;Cleves et al 2014;Erickson et al 2014Erickson et al , 2015Erickson et al , 2016Glazer et al 2014Glazer et al , 2015Liu et al 2014;Terekhanova et al 2014;…”
Section: Population Genomic Analysesmentioning
confidence: 99%